Investing in sports stocks : a case of Sportfolio Management Inc. - Chard, Chris (London : Human Kinetics, Inc., 2017)
Jordan Bourne is the Chief Executive Officer (CEO) of Sportfolio Management Inc. (SMI), a small hedge fund operating out of Boston, Mass. SMI provides prudent and profitable investment management services to clients through active investment in publicly traded companies operating in sport-related business endeavors. By employing both "long" and "short" investment management strategies, Bourne's objective is to achieve a positive rate of return in the Sportfolio for her valued clients. Assistance from the firm's Investment Analysts is vital to meet this objective.
Originally Published InChard, C. (2017). Investing in sports stocks: A case of Sportfolio Management Inc. Case Studies in Sport Management, 6(1), 71-75.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Sportfolio Management Inc. (SMI); Hedge funds -- Boston (Mass.) -- Case studies; Financial services industry -- Boston (Mass.) -- Case studies; Sports -- Economic aspects -- Case studies